STEM AT HOME MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA PADA TOPIK PESAWAT SEDERHANA - Zalya, Anisa Putri; Zulirfan, Z; Azizawwati, Azizahwati; Feniwati, Feniwati (Journal of Indonesian Science Teachers, 2025)
Creative thinking skills are one of the 21st-century skills that students must have to utilize their knowledge well and easily adapt to the times. However, science learning in schools still rarely uses the right learning media to stimulate students' creative thinking skills. Therefore, efforts are needed from science educators to facilitate students with effective learning media to train students' creative thinking skills. This research aims to examine the effectiveness of using the STEM at Home Kit in learning simple machine in improving students' creative thinking skills. The research used quasi-experimental method with posttest-only control group design. The research subjects were VIII grade students of SMP Negeri 13 Pekanbaru consisting of two classes: the experimental class using the STEM at Home KIT and the control class using the SMP science standard KIT. The instrument used was creative thinking skills test. The results showed that the average creative thinking skills of students in the experimental class increased significantly compared to the control class. The use of the STEM at Home KIT trains students to understand the concept of simple machine contextually and can train students' creative thinking skills. Students' responses to learning with the STEM at Home KIT were also very positive, because they were considered interesting, easy to use, and relevant to the concepts taught. This research concludes that the STEM at Home KIT is effectively used in learning simple machine to improve students' creative thinking skills, as well as providing a more meaningful and enjoyable learning experience.